1979
DOI: 10.1099/00221287-115-2-491
|View full text |Cite
|
Sign up to set email alerts
|

Formation, Isolation and Characterization of Trehalose Dimycolates from Rhodococcus erythropolis Grown on n-Alkanes

Abstract: Rhodococcus erythropolis DSM 432 15 produced a surface-active trehalose lipid whose formation was induced by n-alkanes to a maximum of 2.1 g 1-1 in a 50 1 batch culture on 2% (w/v) n-alkanes of chain length C13 to CIS. The glycolipid was extracted from the biomass with n-hexane and was purified by repeated chromatography on silica gel. It contained aptrehalose as the sole non-reducing sugar. The lipid moiety was characterized by 13C nuclear magnetic resonance spectroscopy and mass spectrometry and consisted pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(76 citation statements)
references
References 29 publications
5
70
0
1
Order By: Relevance
“…This is high compared to those of other biosurfactants. For example, glycolipid CMC values range from 27 to 40 mg/ liter for rhamnolipid (5,59) and from 4 to 15 mg/liter for trehalose lipid (19,44), depending on the surfactant components present. For the lipoproteins, CMC values for lichenysin range from 10 to 30 mg/liter (18,23,58), and for surfactin, iturin, and fengycin, reported CMC values are 10, 20, and 11 mg/liter, respectively (12).…”
Section: Resultsmentioning
confidence: 99%
“…This is high compared to those of other biosurfactants. For example, glycolipid CMC values range from 27 to 40 mg/ liter for rhamnolipid (5,59) and from 4 to 15 mg/liter for trehalose lipid (19,44), depending on the surfactant components present. For the lipoproteins, CMC values for lichenysin range from 10 to 30 mg/liter (18,23,58), and for surfactin, iturin, and fengycin, reported CMC values are 10, 20, and 11 mg/liter, respectively (12).…”
Section: Resultsmentioning
confidence: 99%
“…One major class of biosurfactants is the glycolipids, which includes rhamnolipids, trehalose lipids, and sophorose lipids. Rhamnolipids are produced only by P. aeruginosa (30,33); trehalose lipids are produced only by a number of closely related genera, including Rhodococcus, Nocardia, Corynebacterium, Tsukamurella, Gordonia, Mycobacterium, and Arthrobacter, all belonging to the Firmicutes division (3,12,31,44); and sophorose lipids are produced by several species of Candida (14,15,22). A newly identified glycolipid group called mannosylerthritol lipids are produced by Candida and Ustilago maydis (25,26,51).…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that hydrocarbon-utilizing microorganisms accumulate lipids readily. Such microorganisms are provided with hydrophobic envelopes that make them bind easily to hydrophobic compounds [14,15]. It has been suggested that a high cell lipid content is necessary for the uptake of hydrocarbons [16,17].…”
Section: Discussionmentioning
confidence: 99%